2004
DOI: 10.1088/0964-1726/13/5/014
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical transduction in multilayer ionic transducers

Abstract: A transducer consisting of multiple layers of ionic polymer material is developed for applications in sensing, actuation and control. A multilayer transducer is fabricated by layering individual transducers on top of one another. Each multilayer transducer consists of two to four individual layers each approximately 200 µm thick. The electrical characteristics of the transducers can be varied by connecting the layers in either a parallel arrangement or a series arrangement. The tradeoff in deflection and forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
39
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 7 publications
(12 reference statements)
1
39
0
Order By: Relevance
“…[4][5][6][7] Since then, much research effort has been devoted to this class of EAPs with the objective of further improving the electromechanical performance properties such as the actuation speed, strain level, and efficiency. [4][5][6][7][8][9][10][11][12][13][14] Figure 1͑a͒ illustrates schematically such an ionic polymer bending actuator in which the accumulation and depletion of cations at the cathode and anode, respectively, create bending of the ionic polymer membrane under an electrical signal. Experimental results have indicated that a high population of the excess charges at the electrodes is highly desirable in order to generate high electromechanical actuation.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…[4][5][6][7] Since then, much research effort has been devoted to this class of EAPs with the objective of further improving the electromechanical performance properties such as the actuation speed, strain level, and efficiency. [4][5][6][7][8][9][10][11][12][13][14] Figure 1͑a͒ illustrates schematically such an ionic polymer bending actuator in which the accumulation and depletion of cations at the cathode and anode, respectively, create bending of the ionic polymer membrane under an electrical signal. Experimental results have indicated that a high population of the excess charges at the electrodes is highly desirable in order to generate high electromechanical actuation.…”
mentioning
confidence: 99%
“…To realize that, porous electrodes which offer large electrode areas in contact with ionomers are often utilized in this class of actuators. [4][5][6][7][8][9][10][11][12][13][14] One widely investigated ionic polymer metal composite ͑IPMC͒ uses a chemical reduction method to deposit precious metals to Nafion ͑a perfluorosulfonated ionomer developed by DuPont͒ membrane surfaces, in which nanosized metal particles penetrate into the Nafion membrane to form porous electrodes. [5][6][7]11,14 More recently, a direct assembly method in which conductive nanoparticles were mixed with a Nafion ͑or an ionomer͒ solution and this mixture is directly deposited on the Nafion ͑or an ionomer͒ membrane to fabricate IPMC was developed.…”
mentioning
confidence: 99%
See 3 more Smart Citations